The Influence of Service Quality on Customer Satisfaction of Regional Drinking Water Company (PDAM) “Delta Tirta” - Iva Mareta Dewi; Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2022)
Good public services are services that can meet Servqual indicators, that’s tangible, reliability, responsiveness, assurance, and empathy. However, there are still many services that are not good. The problems that occur in PDAM